Seric and hepatic NTPDase and 5′ nucleotidase activities of rats experimentally infected by Fasciola hepatica - Doleski P.H. (2016)
© 2016 Cambridge University Press.The enzymatic activities of NTPDase and 5′nucleotidase are important to regulate the concentration of adenine nucleotides, known molecules involved in many physiological functions. Therefore, the objective of this study was to evaluate the activity of NTPDase and 5′nucleotidase in serum and liver tissue of rats infected by Fasciola hepatica. Rats were divided into two groups: uninfected control and infected. NTPDase activity for adenosine triphosphate (ATP) and ADP substrates in the liver was higher compared with the control group at 15 days post-infection (PI), while seric activity was lower. In addition, seric and hepatic samples did not show changes for 5′nucleotidase activity at this time. On the other hand, either NTPDase or 5′nucleotidase activities in liver homogenate and serum were higher at 87 days PI. Early in the infection, low NTPDase activity maintains an increase of ATP in the bloodstream in order to activate host immune response, while in hepatic tissue it decreases extracellular ATP to maintain a low inflammatory response in the tissue. As stated, higher NTPDase and 5′nucleotidase activities 87 days after infection in serum and tissue, probably results on an increased concentration of adenosine molecule which stimulates a Th2 immune response. Thus, it is possible to conclude that F. hepatica infections lead to different levels of nucleotide degradation when considering the two stages of infection studied, which influences the inflammatory and pathological processes developed by the purinergic system.